Palestinian Problem: Peace Resistance or Cyclic Return to Deadlock - T M Khalayla (RUDN Journal of Political Science, 2014)
This article considers the phenomenon of peaceful resistance, which is maintained by Palestinians amid the Israeli-Palestinian conflict. The main thesis of the article lies in the problem of effectiveness of this method under conditions of indifference and lack of interest of the Western news agencies in this relation, as well as the liability of the State of Israel, which ignores all the peace initiatives. Conclusion of the article deposes that in such circumstances, there can appear new radical groups who will abandon an unarmed method as ineffective that will lead to an escalation of the conflict.